2021
DOI: 10.1111/bph.15701
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 promotes migration and differentiation of epidermal cells during wound healing via SIRT1‐dependent autophagy

Abstract: Background and Purpose Migration and differentiation of epidermal cells are essential for epidermal regeneration during wound healing. Fibroblast growth factor 21 (FGF21) plays key roles in mediating a variety of biological activities. However, its role in skin wound healing remains unknown. Experimental Approach Fgf21 knockout (Fgf21 KO) mice were used to determine the effect of FGF21 on wound healing. The source of FGF21 and its target cells were determined by immunohistochemistry, immunoblotting, and ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…FGF21 has been reported to act in a paracrine fashion to promote cell migration and differentiation during wound healing and to act in a dual paracrine fashion to increase KGF expression, promoting fibroblast activation in skin fibrosis. These findings are consistent with the mechanism of action of FGF21 observed in this study [ 45 , 46 ]. FGF21 is mainly secreted by the liver and adipose tissue, with these tissues being important sources of FGF21 in some diseases [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…FGF21 has been reported to act in a paracrine fashion to promote cell migration and differentiation during wound healing and to act in a dual paracrine fashion to increase KGF expression, promoting fibroblast activation in skin fibrosis. These findings are consistent with the mechanism of action of FGF21 observed in this study [ 45 , 46 ]. FGF21 is mainly secreted by the liver and adipose tissue, with these tissues being important sources of FGF21 in some diseases [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Autophagy has recently been found to play an essential role in the regulation of many types of cell migration [35][36][37], but the related mechanisms are not fully understood. Bressan and Saghatelyan showed that AMPKinduced autophagy is a key regulator of cell migration and plays an important role in the recycling of the focal adhesion molecule paxillin [38].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified that SIRT1 is downregulated in PD, and upregulating SIRT1 is neuroprotective against MPTP-mediated neurotoxicity (Singh et al, 2017 ). Of interest, more recent studies have shown that the effects of FGF21 are highly related to SIRT1 expression (Chen et al, 2021 ), and SIRT promoted FGF21 sensitivity neuronal cells (Matsui et al, 2018 ). We then examined the SIRT1 expression in PD models, and our results showed that FGF21 significantly upregulated the SIRT1 expression and inhibited the activation of the NF-κB pathway both in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%